Big data and smart service systems - Liu, Xiwei; Anand, Rangachari; Xiong, Gang; Shang, Xiuqin; Liu, Xiaoming (Intelligent systems series., 2017)
Big Data and Smart Service Systems presents the theories and applications regarding Big Data and smart service systems, data acquisition, smart cities, business decision-making support, and smart service design. The rapid development of computer and Internet technologies has led the world to the era of Big Data. Big Data technologies are widely used, which has brought unprecedented impacts on traditional industries and lifestyle. More and more governments, business sectors, and institutions begin to realize data is becoming the most valuable asset and its analysis is becoming the core competitiveness.